To Serve the Community or Oneself: The Public Servant's Dilemma - Barr, Abigail; Lindelöw, Magnus; Serneels, Pieter (World Bank, Washington, D.C., 2013)
Embezzlement of resources is hampering public service delivery throughout the developing world. Research on this issue is hindered by problems of measurement. To overcome these problems, the authors use an economic experiment to investigate the determinants of corrupt behavior. They focus on three aspects of behavior: 1) Embezzling by public servants. 2) Monitoring effort by designated monitors. 3) Voting by community members when provided with an opportunity to select a monitor. The experiment allows the authors to study the effect of wages, effort observance, rules for monitor assignment, and professional norms. Their experimental subjects are Ethiopian nursing students. The authors find that service providers who earn more embezzle less, although the effect is small. Embezzlement is also lower when observance (associated with the risk of being caught and sanctioned) is high, and when service providers face an elected, rather than a randomly selected monitor. Monitors put more effort into monitoring when they face reelection, and when the public servant receives a higher wage. Communities reelect monitors who put more effort into exposing embezzlement. Framing-whereby players are referred to as "health workers" and "community members" rather than by abstract labels-affects neither mean embezzlement nor mean monitoring effort, but significantly increases the variance in both. This suggests that different types of experimental subjects respond differently to the framing, possibly because they adhere to different norms.